Vernacular heritage as urban place-making: activities and positions in the reconstruction of monuments after the Gorkha Earthquake in Nepal, 2015-2020: the case of Patan - Brosius, Christiane; Michaels, Axel (Sustainability, 2020)
In an analysis of the reconstruction measures in the old city or Lalitpur (Patan) after the 2015 earthquakes in Nepal, it is shown that, contrary to usual assumptions, the reconstruction was not only concentrated on the prominent, strongly internationally promoted and financed world cultural heritage sites, but took also place at smaller sites—especially at arcaded platform (phalcā), small monasteries and shrines throughout the city. While the larger royal squares, often at the heart of tourism and heritage policies, are important for the status and hierarchy of kings, queens and associated castes, the smaller and possibly less visually spectacular buildings and rituals ‘off the 5-Star map’ (the intangible heritage) are not less and are possibly even more relevant to inhabitants. Understanding this intangible heritage requires a different approach to what heritage means and how it is experienced from a more vernacular perspective. Rather than being firmly defined, heritage, and the reconstruction thereof, dynamically and controversially shapes how the disaster of the earthquake has been experienced, and is also connected to larger discourses on urban and social transformation and to concepts of ethnicity, nation and citizenship as well as social, symbolic prestige and economic status and distinction. The Gorkha Earthquakes have also produced a rich field of vernacular heritage formations and processes that enable us to consider heritage as placemaking. In this context, controversial concepts like ‘authenticity’ as well as various qualities and temporalities of ‘community’ participation and formation should be considered.
Gesehen am 19.11.2020